KAJIAN PENERAPAN INTRANET PADA LEMBAGA TINGGI NEGARA BERDASARKAN TAM: STUDI KASUS DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA - Imron Imron (LPPM Universitas Bina Sarana Informatika, 2013)
This center information technology infrastructure to be one that should not be overlookedespecially in today's digital era. Hardware, software, network devices, and users become adecisive element in the creation of inter-related and quality informationmsystems. The trendinvolving the end user (end user computing) in the computerization process shows that the processof processing data into information for decision-making involves a user role. The results ofinformation technology experts in software development has spawned a trend of sustainabletechnical age and age ekonomsmshorter. The presence of new software to replace the old softwareis always followed by ease of use for users. from the original client-server basis, so nowdeveloping a web-based applications that run via the internet and intranet. But because of the useof technology also involves the human element had to know the level ofacceptanceninmtheouse0ofmthe0application. The research aims to examine the implementation ofIntranet Information System as one application of information technology, using the approach ofTechnology Acceptance Model (TAM) were tested with path analysis using the software AmosKeywords: Web-Based Information System, Government, Information Technology, Networking, Technology Acceptance Model (TAM), Path Analysis, Path Analysis.